Comparison of robotic and open partial nephrectomy: Single-surgeon matched cohort study - Oh, Jong Jin; Byun, Seoksoo; Hong, Sung Kyu; Jeong, Chang Wook; Lee, Sang Eun (Canadian Urological Association Journal, 2014)
Introduction: We present comparative outcomes among matched patients who underwent robotic partial nephrectomy (RPN) or open partial nephrectomy (OPN) by a single surgeon at a single institution. Methods: We reviewed the medical records of 200 patients who underwent RPN (n = 100) or OPN (n = 100) between May 2003 and May 2013. The patients who underwent RPN were matched for age, gender, body mass index (BMI), American Society of Anesthesiologists (ASA) score, as well as tumour size, side and location. Perioperative outcomes were compared. Results: There was no significant difference between the 2 cohorts with respect to patient age, BMI, ASA score, preoperative glomerular filtration rate, tumour size and the R.E.N.A.L. nephrometry score. The mean operative time was longer in the RPN group, but there were no significant differences with respect to warm ischemic time and postoperative renal function. The length of hospitalization and use of postoperative analgesics (ketoprofen) were more favourable in the RPN cohort. There was no significant difference in the mean estimated blood loss, transfusion rate, or complications between the cohorts. Conclusions: Considering the perioperative and postoperative parameters, RPN is a viable option as a nephron-sparing surgical procedure for small renal masses that yields outcomes comparable to those achieved with OPN. Despite matched cohort analysis among patients who underwent PN by a single surgeon, there may be inherent selection bias; therefore future prospective trials are needed.